Status of forest reserve and forest management capabilities in Soutrhwestern Nigeria (2011)
The need for sustainable forest management cannot be over emphasized if the economic benefits of forests were to be met without ecological consequences. This pacer reports the prospect of sustainable forest management in the context of managerial capability in southwestern Nigeria, which is housing most of the forest resources relics in the county. The study was carried out in the South West geopolitical zone of Nigeria comprising Lagos, Ogun, Oyo, Osun, Ondo, and Ekiti States using multi-stage random sampling. The target population for the study comprised the local inhabitants, forest management personnel and timber contractors/saw milers in each state. Information was sourced from each group using three sets of structured questionnaire and Focus Group Discussions (FGDs) involving group of people of the same sex and age groups from each target population. Secondary data were also obtained from State Forestry Departments and archives. Information garnered was analysed using descriptive statistics. Findings revealed that all forest reserves in Osun, Ondo, Ogun and Lagos States have been intensively encroached upon; however the extent of the encroachment has not been fully established due to lack of adequate data in all the states. Most (98.6%) of the local inhabitants opined that the state government is solely responsible for the management of the forest reserves in the study area. The timber contractors /saw millers perceived law enforcement on forestry activities as low in Osun state (32.4%) and Lagos states (29.4%) but moderate in Ondo (42.3%) and Ogun states (26.5%). More importantly was the observation that government is more interested in revenue generation from the forests rather than their sustainable management, which 33.0% of the timber contractors/saw millers Inferred as responsible for the low regeneration drive from the sector. An average of 47.1% and 42.3% of the forest officials were also of the opinion that forest management in all the four states sampled was bad and very bad respectively. FGDs among them revealed that state governments have not gotten the capabilities of managing the forest estates effectively and efficiently. Their suggestions for mitigating the present management constraints centered on commensurable increase in the staff strength in Nigeria's Forestry Departments to meet forest extent and forest activities. Inappropriate policy framework was identified by all respondents as the underlying causes of much forest loss. The forestry official proffered preparation of management plan for each forest reserve (56.3%). education of stakeholders on sustainable management (17.6%), massive afforestation programme (36.6%) as well as private and community participation (31.7%) as sustainable forest management strategies.